Pengembangan Aplikasi Edukasi Kuis Bahasa Arab sebagai Alternatif Media Belajar Siswa Kelas I Madrasah Ibtidaiyah - Firdhany Nur Azizah; Hamdan Husein Batubara (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2021)
Vocabulary is one of the most critical linguistic components that Arabic as a foreign language learners must master. Previous studies discovered that it was accurate that first-grade students struggled to recognize and master Arabic vocabularies since the learning process mainly consisted of lectures and homework. Students need external help or stimulation to increase their comprehension of Arabic. Educational games may encourage first-grade students since they like to play and explore electronic devices such as androids, laptops, and so on. This study aims to develop an educational application that contains acceptable Arabic vocabulary content for first grade (elementary school) students. The research employed the ADDIE (Analysis-Design-Development-Implementation-Evaluation) paradigm of research and development. This study involves developing an educational application called